Tradisi Lisan Mamongoti Bagas (Memasuki Rumah Baru) dalam Masyarakat Batak Toba - HELERI MARIANI SINABUTAR (Balai Bahasa Sumatera Utara, 2019)
This research discuss about the oral tradition mamongoti bagas ( enter new house) in Batak Toba society. The theory used is theory text, kotex and the context and local wisdom .The Method used is descriptive qualitative. The data is series of the event enter new house in Batak Toba society.The results show that text in the event enter a new house in Batak Toba society has a meaning to form new social relationships. Kotex contains elements prosemik where there is a pause of speakers, sotah we know position of person in the event enter a new house in Batak Toba society. The context is about context situation, social and place.The event enter new house contains three local wisdom, namely thanksgiving, harmony and peace, and caring environment. It can be concluded that oral tradition enter a new house in batak toba society contains local wisdom tah must be protected and preserved.Key Words : mamongoti bagas, Batak Toba Society, oral tradition, local wisdom